PROBLEMS OF IT DEPARTMENT IN A MEDICAL UNIVERSITY - V. Ya Gelman; A. A. Tikhomirova (Образование и наука)
The aim of the study is the analysis of the problems faced by heads and staff of IT departments in medical universities. Methodology and research methods. The methods involve expert estimation, analysis and generalization of practical work experience of IT departments. Results and scientific novelty. The main aspects and specifics of professional activity of IT departments of modern medical schools are designated. The approaches to the definition of the hierarchy of goals in the professional activities of the department, as well as quantitative and qualitative indicators that assess the effectiveness of their achievements are analyzed. The contradictions arising between long-term and short-term goals of the IT department are highlighted. The main challenges which heads of IT departments can deal with in the course of day-to-day management work planning are described. The problems arising in educational, educational-methodical and scientific work of department, in its economic activity, solution of personnel affairs, and aspects of material support are considered. The possible solutions to these problems are proposed. Practical significance. The results of the analysis, proposed approaches and practical recommendations will enable to better organize the work of the IT department in a medical school. The advantage of the proposed approaches consists in their versatility: with some adjustment, they can be used by other departments, regardless of the specifics and the type of educational institution.